Global prevalence and incidence of pressure injuries in hospitalised adult patients: A systematic review and meta-analysis. (May 2020) - Li, Zhaoyu; Lin, Frances; Thalib, Lukman; Chaboyer, Wendy
Abstract: Background: Pressure injuries are frequently occurred adverse events in hospitals, affecting the well-being of patients and causing considerable financial burden to healthcare systems. However, the estimates of prevalence, incidence and hospital-acquired rate of pressure injury in hospitalised patients vary considerably in relevant published studies. Objectives: To systematically quantify the prevalence and incidence of pressure injuries and the hospital-acquired pressure injuries rate in hospitalised adult patients and identify the most frequently occurring pressure injury stage(s) and affected anatomical location(s). Design: Systematic review and meta-analysis. Data sources: Medline, PubMed, Embase, Cochrane Library, CINAHL and ProQuest databases from January 2008 to December 2018. Review methods: We included studies with observational, cross-sectional or longitudinal designs, reporting pressure injury among hospitalised adults (≥16 years) and published in English. Outcomes were point prevalence, incidence of pressure injuries and the hospital-acquired pressure injuries rate reported as percentages. Two reviewers independently appraised the methodological quality of included studies. Heterogeneity was assessed by using the I² statistic and random effects models were employed. Sources of heterogeneity were investigated by subgroup analysis and meta-regression. Results: Of 7, 489 studies identified, 42 were included in the systematic review and 39 of them were eligible for meta-analysis, with a total sample of 2, 579, 049 patients. The pooled prevalence of 1, 366, 848 patients was 12.8% (95% CI 11.8–13.9%); pooled incidence rate of 681, 885 patients was 5.4 per 10, 000 patient-days (95% CI 3.4–7.8) and pooled hospital-acquired pressure injuries rate of 1, 893, 593 was 8.4% (95% CI 7.6–9.3%). Stages were reported in 16 studies (132, 530 patients with 12, 041 pressure injuries). The most frequently occurred stages were Stage I (43.5%) and Stage II (28.0%). The most affected body sites were sacrum, heels and hip. Significant heterogeneity was noted across some geographic regions. Meta-regression showed that the year of data collection, mean age and gender were independent predictors, explaining 67% variability in the prevalence of pressure injuries. The year of data collection and age alone explained 93% of variability in hospital-acquired pressure injuries rate. Conclusion: This study suggested that the burden of pressure injuries remains substantial with over one in ten adult patients admitted to hospitals affected. Superficial pressure injuries, such as Stage I and II, are most common stages and are preventable. Our results highlight healthcare institutions' focus on pressure injuries globally and supports the need to dedicate resources to prevention and treatment on pressure injuries. Registration number: PROSPERO CRD42019118774.